2019
DOI: 10.1021/acs.energyfuels.9b02585
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of a CoMo Catalyst during Catalytic Hydropyrolysis of Biomass. Part 2. Characterization of the Spent Catalysts and Char

Abstract: In this work sulfided CoMo/MgAl 2 O 4 catalysts used in fluid bed catalytic hydropyrolysis for the conversion 12 of beech wood and wheat straw to liquid fuels were thoroughly characterized by Raman spectroscopy and 13 scanning (transmission) electron microscopy together with energy dispersive X-ray spectroscopy. Potassium 14 and calcium were transferred from the beech wood to the catalyst and the accumulated amounts increased 15 proportionally with the time on stream (TOS) and reached 0.67 and 0.28 wt.% after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Stummann et al also found that CoMo catalyst could promote the occurrence of direct deoxygenation of phenols with the lowest content of carbon after the catalytic hydropyrolysis process. In their follow-up research, Stummann et al , studied the coking and deactivation process of the CoMo catalyst and reported the catalytic effect on the products during the semicontinuous operation. A significant increase in the oxygen content of the organic phase in the bio-oil production was found after 5 days of intermittent operation without renewing the catalyst, indicating that the CoMo catalyst gradually lost its catalytic performance.…”
Section: Biomass Catalytic Pyrolysismentioning
confidence: 99%
“…Stummann et al also found that CoMo catalyst could promote the occurrence of direct deoxygenation of phenols with the lowest content of carbon after the catalytic hydropyrolysis process. In their follow-up research, Stummann et al , studied the coking and deactivation process of the CoMo catalyst and reported the catalytic effect on the products during the semicontinuous operation. A significant increase in the oxygen content of the organic phase in the bio-oil production was found after 5 days of intermittent operation without renewing the catalyst, indicating that the CoMo catalyst gradually lost its catalytic performance.…”
Section: Biomass Catalytic Pyrolysismentioning
confidence: 99%
“…32 Therefore it is certain that some deactivation of the catalyst in the HDO reactor has taken place. The catalyst in the fluid bed reactor operates under more harsh conditions and has also been partly deactivated due to carbon deposition and uptake of potassium as will be discussed in detail in part 2 of this work (see ref 35). It is possible to regenerate some of the catalyst activity lost due to coking, 29 while catalyst deactivation due to metals deposited on the catalyst are less reversible 53 and thus of greater concern.…”
Section: (B) the Density At 40mentioning
confidence: 99%
“…Secondly, the effect of poisoning the catalyst by doping it with potassium, in the form of K 2 CO 3 , was studied. In this work (part 1) we report detailed product characterization including the composition of the condensed liquids, while in part 2 35 we characterize the spent catalysts and the produced char in detail. This is to our knowledge the first study in the open literature where the effect of the time on stream on catalytic hydropyrolysis with a well-defined catalyst is tested and the effect of potassium on the catalytic activity in catalytic hydropyrolysis of biomass is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…129 This indicates a very high mobility of K, while Ca was mainly found as larger particles on the spent catalysts. 130 Replacing the complete inventory of expensive zeolite catalyst after 10−20 days of operation makes in-situ CFP with zeolite-based catalysts commercially less attractive, although regeneration by washing in a mild acidic solution may be possible while adding operational costs. 438 Noble metals such as Pt and transition metals like Cu and especially Ni may also be deactivated by sulfur (S) species such as H 2 S, RSH, RSSR, etc., via formation of sulfides, which are difficult to remove due to the formation of a strong metal-S bond.…”
Section: Deactivationmentioning
confidence: 99%
“…50,125−129 Also with HDO catalysts where acidity is not necessarily important, alkali metal may deactivate the catalyst. 130,131 In addition, the separation of char and catalyst fines may be challenging. In ex-situ CFP and CFHP, the ash-rich char can be separated by hot gas filtration, thereby preventing direct contact of biomass ash species with the catalyst, greatly reducing the risk of catalyst poisoning.…”
Section: Introductionmentioning
confidence: 99%